Relative abundance and growth of male and female Nemipterus furcosus population - Amira, F.S.; Rahman, M.M.; Kamaruzzaman, B.Y.; Jalal, K.C.A.; Hossain, M.Y.; Khan, N.S. (Universiti Kebangsaan Malaysia, 2016)
A study was conducted to understand the relative abundance and growth of male and female Nemipterus furcosus population in the Pahang coastal water, Malaysia. The sampling was done monthly for a period of one year. A total of 1446 fish specimens were studied in this research. The results showed that male N. furcosus population was significantly more than female (p<0.01) N. furcosus population. The growth coefficient (b value) varied between 2.6808 and 3.2396 for male and 2.0926 and 3.2838 for female N. furcosus. The growth co-efficients of male N. furcosus were significantly different than the growth co-efficients of female N. furcosus in all months (p<0.05). They showed negative allometric growths in February- June and September. Female N. furcosus showed positive allometric growths in November-January and August. Isometric growths of female were observed only in October and July. As for male N. furcosus, negative allometric growths were observed in March-June, November and January. Male N. furcosus showed positive allometric growths in August, September, October, December and February. Male N. furcosus showed isometric growth only in July. The overall mean condition factor of male and female was statistically similar (p>0.05). The condition factor (K) ranged from 1.2559 to 1.3917 for male while 1.2503 to 1.3926 for female N. furcosus. Overall, higher mean condition factor was observed in smaller fish of both sexes. This study is useful for policy makers and fishery biologists for sustainable fishery management in the Pahang coastal water, Malaysia.